Elements of Carnival as a Mirror of the Protagonists' Insanity in Strangers on a Train - Nadal-Ruiz, Alejandro (FOCUS: Papers in English Literary and Cultural Studies, 2020)
Given Hitchcock’s fascination with the carnivalesque, the novel Strangers on a Train and its film adaptation engage in a dialogue where the amusement park is the focal point. Even if Hitchcock deviates from the novel by returning to the funfair at the end, what is sought with such reappearance is to draw attention to the key role of carnival as a reflection of the strangers’ mental disorder. Although a number of studies deal with the relationship between the two strangers, there is little research that provides an in-depth analysis of the close relationship between carnival and the two protagonists’ mental imbalance. Hence, this article provides a thorough study of how carnival elements mirror the protagonists’ insanity and, most interestingly, to propose a comparative analysis that paves the way for new insights into the relationship between the novel and its film adaptation. Accordingly, this article aims to shed light on how the use of carnival elements in both Highsmith’s Strangers on a Train and its film adaptation by Hitchcock enhances the two strangers’ mental instability.